Comparative Analysis of Components Involved in the Synthesis of Cellulose in Agave Species - María José García-Castillo; Yahaira de Jesús Tamayo-Ordóñez; María Concepción Tamayo-Ordóñez; Felipe Barredo-Pool; Luis Carlos Rodríguez-Zapata; Benjamin Abraham Ayíl-Gutiérrez; María Teresa Pulido-Salas; Lorenzo Felipe Sánchez-Teyer (Agronomy, 2025)
The process of obtaining Agave L. fibers dates back to pre-Hispanic times, and although humans have obtained different products from this crop, to date, the impact of humans (artificial selection, domestication and intensive cultivation) on these species is unknown. In this study, the expression of the CesA gene was evaluated in three species, namely, Agave L, A. sisalana Perrine and A. fourcroydes Lem. (Sac ki), both of which are used for fiber production, and Agave tequilana Weber. The results revealed that, compared with A. fourcroydes and A. tequilana, A. sisalana had a greater leaf area, a significantly greater cellulose content and a greater number of cellulose fibrils. In terms of cell organization, the number and size of sclerenchyma fibers were similar between A. sisalana and A. fourcroydes. However, the relative expression of the CesA gene was five times greater in A. fourcroydes than in A. sisalana and A. tequilana, in contrast with the number of copies in those genomes. In addition, the tertiary structure of the CESA protein in fiber-producing species was modeled, placing agaves in a group along with Populus, Linum, Corchorus and Boehmeria. The haplotype network analysis revealed that A. tequilana is closely grouped with species of the order Poales, unlike the rest of the fiber-producing agaves, which formed a unique cluster. These findings suggest that artificial selection by humans, for various purposes, has contributed to the specialization of genes associated with traits such as fiber production.